Cost-effectiveness of abatacept, tocilizumab and TNF-inhibitors compared with rituximab as second-line biologic drug in rheumatoid arthritis - Huoponen S.; Aaltonen K.J.; Viikinkoski J.; Rutanen J.; Relas H.; Taimen K.; Puolakka K.; Nordström D.; Blom M. (PUBLIC LIBRARY SCIENCE, 2022)
Objectives: The objective of this study was to evaluate the cost-effectiveness of abatacept, tocilizumab, and tumor necrosis factor (TNF) inhibitors as compared with rituximab in Finnish rheumatoid arthritis patients, who have previously been treated with TNF inhibitors.
Methods: A patient-level simulation model was developed to predict costs and outcomes associated with four biological drugs (abatacept, tocilizumab, rituximab and TNF inhibitors) in the treatment of rheumatoid arthritis. Following lack of efficacy or adverse events, the patients were switched to another biological drug until all four options were exhausted. After that, the patients were assumed to receive a 6th line treatment until death. The patients' baseline characteristics and regression models used in the simulation were based on observational data from the National Register for Biological Treatments in Finland. Direct costs comprised drug costs, administration costs, costs of switching, and outpatient and inpatient care, while indirect costs included disability pension and sick leaves due to rheumatoid arthritis. Several subgroup and deterministic sensitivity analyses were conducted.
Results: Drug costs were the lowest for rituximab, but when administration costs and costs of switching were included, drug costs were the lowest for TNF inhibitors. Abatacept was associated with the highest drug costs, whereas rituximab was associated with the highest healthcare costs. In total, TNF inhibitors had the lowest direct costs, while rituximab had the highest direct costs. The amount of quality-adjusted life years (QALY) gained ranged from 9.405 for rituximab to 9.661 for TNF inhibitors. TNF inhibitors, abatacept, and tocilizumab were dominant in comparison to RTX.
Conclusions: TNF inhibitors, abatacept, and tocilizumab had lower costs and higher QALYs than rituximab, and therefore, they were dominant in comparison to rituximab. As TNF inhibitors had the lowest costs and highest QALYs, they were the most cost-effective treatment option.